The Stieda process of the talus: the anatomical knowledge and clinical significance of an overlooked protrusion - Eren Ogut (Bulletin of the National Research Centre, 2022)
Abstract Background The Stieda process (SP) is an extended lateral tubercle of the posterior process of the talus. Although there are different classifications for SP in the literature, it is essential to know the differential diagnosis of SP from fractures and accessory ossicles. This review aims to classify the SP and to guide the formation, prevalence, etiopathology, symptoms, differential diagnosis, and treatment. Main body of the abstract The authors conducted a literature review that lasted up to September 2022 and used the databases PubMed, Web of Science, and Google Scholar to explore the SP of the talus in all of its aspects. Out of 3802 publications, only 34 could be included, and most of them were studies on posterior ankle impingement syndrome (PAIS). The occurrence, prevalence, etiopathology, clinical significance, symptoms, differential diagnosis, and treatment methods of SP were investigated based on the literature. SP is formed by the fusion of a secondary ossification center at the posterolateral side of the talus with an incidence of 12–36.5%. It is frequently observed in males. It causes reduced plantar flexion, impairment in the inversion of the foot, pain, and swelling in the posterior ankle joint, PAIS, and SP fractures after trauma. Short conclusion SP can be diagnosed by lateral ankle radiography or MRI in patients complaining of PAIS. The initial treatment of the SP should include reducing inflammation, swelling, pain, and limiting activities. If neither modality affects the patient, surgical treatment will be performed, and SP will be resected until the impingement disappears.